Willingness to trade-off: An intermediate factor in patient decision-making regarding escalating care - Elizabeth K Seng; Amy S Grinberg; Liana Fraenkel (Health Psychology Open, 2018)
This study aimed to evaluate treatment necessity, treatment concern, and willingness to engage in decisional trade-offs in the context of treatment escalation decision-making. Participants ( n  = 147) recruited online were randomized to read a vignette about escalating care in psoriasis in a 2 (high treatment concern vs moderate treatment concern) × 2 (high perceived treatment necessity vs moderate perceived treatment necessity) design. High treatment concern was associated with choosing to defer treatment escalation and being unwilling to engage in decisional trade-offs if disease risk changed. Results highlight the importance of treatment concern and willingness trade-off in treatment escalation decision-making.